2012
DOI: 10.1259/dmfr/27670911
|View full text |Cite
|
Sign up to set email alerts
|

Influence of scan setting selections on root canal visibility with cone beam CT

Abstract: Objectives: The aim of this study was to assess the influence of scan setting selection, including field of view (FOV) ranging from small to large, number of projections and scan modes on the visibility of the root canal with cone beam CT (CBCT). Methods: One human mandible cadaver was scanned with CBCT (Accuitomo 170; J Morita MPG Corp., Kyoto, Japan) using six different FOVs (464 cm, 666 cm, 868 cm, 10610 cm, 14610 cm and 17612 cm) with either 360 or 180 projections in standard and high resolution. The right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 18 publications
(22 reference statements)
0
33
0
12
Order By: Relevance
“…In that study, a cadaver mandible was, respectively, scanned at a standard-and high-resolution mode of the Accuitomo 170 CBCT system (J Morita USA, Irvine, CA), and the results showed that the standard scan mode did not have a negative influence. 5 In another study, the detection accuracy of condylar erosions was assessed with CBCT images scanned using different voxel sizes and FOVs. The results showed that, for assessment of bony erosions, the CBCT images acquired with a 6-inch FOV at 0.2-mm voxel size were significantly better than the images acquired with a 12-inch FOV at 0.4-mm voxel size in the CB MercuRayÔ (Hitachi Medical, Twinsburgh, OH) CBCT system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, a cadaver mandible was, respectively, scanned at a standard-and high-resolution mode of the Accuitomo 170 CBCT system (J Morita USA, Irvine, CA), and the results showed that the standard scan mode did not have a negative influence. 5 In another study, the detection accuracy of condylar erosions was assessed with CBCT images scanned using different voxel sizes and FOVs. The results showed that, for assessment of bony erosions, the CBCT images acquired with a 6-inch FOV at 0.2-mm voxel size were significantly better than the images acquired with a 12-inch FOV at 0.4-mm voxel size in the CB MercuRayÔ (Hitachi Medical, Twinsburgh, OH) CBCT system.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, another study indicates that the use of high spatial resolution mode for a CBCT scan does not increase the visibility of the root canal space when compared with the images scanned with a standard mode. 5 These inconsistent results demonstrate the necessity of evaluation of various clinical tasks for CBCT images scanned at different spatial resolutions. In the search of literature, we did not find one study exclusively evaluating the impact of spatial resolution on CBCT image for the detection of condylar defects.…”
Section: Introductionmentioning
confidence: 99%
“…CBCT imaging has also been used for the detection of a second mesiobuccal (MB2) root canal in maxillary molars (6,7). However, recent literature showed that the visibility of anatomic structures including the root canal space is dependent on the CBCT machine type and scan settings such as field of view (FOV), number of projections, and resolution (8). In addition, the root filling materials (eg, Gutta-percha and sealer) have been reported to compromise the quality of the images (6,9).…”
mentioning
confidence: 99%
“…Our results differ from those of Panmekiate et al 17 On mandibular linear measurements, no significant differences in the distances were found between the different combinations of peak voltage and milliamperes. Using a human mandible cadaver, Hassan et al 14 showed CBCT scan mode (exposure time) was less relevant on root canal visibility. Kwong et al 12 evaluated subjectively the image quality of head skull CBCT by varying settings (mA and kV) and fields of view.…”
Section: Discussionmentioning
confidence: 99%